(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
The genesis of SomAção, an improvisation system for on-scene sounds, is based on the author’s understanding of listening experiences and models of sound action and interaction, in music-theater and sound-theater. Listening experiences are plurivalent, emergent and situated, encompassing multiple focuses, dimensions and references. Each model of sound action and interaction mobilizes intentions and attitudes, articulating body poetics and listening experiences. Collaborative experiments and reflections with sound action and interaction models such as Support, List, Ostinato, Reading, Melos and Dialog give rise to initial results and reflections on the possibilities and limitations of the system.